From obese to lean curriculum: exploring students’ experiences about developing competencies in medical education - Karami, Morteza; Hashemi, Nooriyah; Van Merrienboer, Jeroen (Frontiers in Medicine, 2024)
Introduction: Since the beginning of the 21st century, competency-based education has been proposed as an approach to education in many disciplines including the medical sciences and it has become a dominant approach in many countries. We aimed to explore the lived experiences of general medical students about developing competencies in the academic curriculum.We conducted a phenomenology method to study lived experiences of general medical students through selecting participants via a purposeful sampling strategy. Snowballing and maximum variation samplings were also applied to recruit additional participants. The study was conducted at a Medical School in Iran. Three successive phases of qualitative data analysis, namely, data reduction by coding, data structuring by categorization, and data interpretation by discussion were applied to analyze the interviews.The results of the research showed that students' lived experiences fall under 4 main themes with 9 subthemes. The main themes show that (1) the compartmentalized curriculum in basic courses is experienced as the missing parts in a puzzle, (2) the physiopathology curriculum is experienced as swimming on land, (3) the externship is experienced as touring a mysterious land, (4) the internship is experienced as unleashed arrows.Discussion: Our findings reveal that despite the changes already made in the curriculum, its compartmentalization is still a main obstacle to achieving competency-based medical education.A strict requirement for leaving the discipline-based curriculum behind is to use an integrated approach, in which basic science courses are connected with clinical cases, and physiopathology courses are connected with externships and internships.